An investigation of glass extrusion for optical fiber preform - Tan, Jing Wen (2016)
Optical fibers have been playing a key role in our daily lives and they are widely used in areas ranging from daily communications to military applications. The main processes involved in producing an optical fiber are manufacturing of the glass optical preform, followed by drawing of optical fiber from the preform and lastly testing of the drawn optical fiber. In this project, the main focus is on fabrication of glass optical preform by billet extrusion method. The project will be split into two parts namely the experiment and the simulation. The experimental objective is to optimize the experimental process so that the glass optical preform fabricated is of good homogeneity with 12 distinct and clear feedholes. ANSYS CFX software is used to simulate billet extrusion process which will act as a guide for the experimental process. The simulated extrusion process and extrusion force value can be monitored when using a specific extrusion speed and temperature as input parameters.